Presenting a green governance model with a sustainable development approach in the health system (case study: Kerman University of Medical Sciences) - zahra roozbeh; shiva madaheyan; amin nikpour (Institute of Management fekrenoandish, 2023)
The present study presented a model of green governance with a sustainable development approach in the health system. The method of this study is applied and analytical in terms of aim, qualitative in terms of process, and grounded theory in terms of data collection and analysis. Twelve experts were first interviewed after examining the theoretical foundations and previous studies. Then, data were analyzed, and categories, related concepts, and semantic codes were extracted to answer the research questions by MAXQDA (2020) software. The interviews continued until theoretical saturation was reached. "Balanced and integrated management," "service provision," and "financial resources" were identified as causal factors. "Legal environment," "political environment," "cultural and social environment," and "technology" were identified as contextual factors. "Government policies" and "change management" were identified as intervening factors. "Green governance affairs," "contractual affairs," and "participatory affairs" were identified as strategies. "Creating alignment between goals, policies, and structure and culture in the health sector," "improving administrative and environmental health," "and dynamism and adapting to changes and developments in the health system" were identified as outcomes. Extended abstract Introduction Significant development caused by the industrial revolution that began in the mid- 1700s led to gradual changes in industries, economic growth, higher standards of living, the availability of world-class products, amenities, etc. However, the environmental aspect was neglected, resulting in much environmental damage (Ferran Vila, Yanez & Miotto, 2022). In recent decades, human beings have well understood the danger of neglecting the environment since all kinds of environmental pollution have endangered the whole earth as a human habitat. Thus, efforts were made to protect the environment and modify development methods. Hence, environmental concerns and sustainable development are among the global community's most significant topics (Seyd Alavi, Mohammad, Ghalavandi, Abbaspour & Mohamadkhni, 2020). Several quantitative and qualitative factors affect sustainable development. However, many thinkers of economics and other sciences argue that governance has a relatively higher rank in affecting sustainable development (Zahiri, Zayanderoody & Jalaie, 2021). Accordingly, green governance as a new and sustainability-based governance model creates new challenges for the traditional human-centered development ideology (Li et al., 2018) and emphasizes the balance between economic growth and sustainable development (Lin, Gui, Xie, & Liu, 2019). Green governance includes the combination of the principles of environmental sustainability and social justice in the decision-making processes of the government and other institutions (Dryzek, 2013). Green governance is also considered a driving force for the restructuring of economic development and the realization of a green technological revolution to realize and achieve sustainable development goals (Xu & Zhu, 2022). Also, health domain and the health system are among the most significant service sectors and indicators of social development and welfare (Seddighi, Nosrati Nejad & Basakha, 2020). Applying the green governance model in the health system can minimize the environmental damage caused by providing services. Despite the role and significance of this strategy, few efforts have been made to apply it, especially in Iran's health system. Thus, the present study fills the existing research gap. It can help the health system use the green governance strategy to achieve its sustainable development goals. Therefore, in this study, the researcher seeks to answer the question of the model of green governance with a sustainable development approach in Iran's health system. Literature review Peyghan, Yaghobi, and Keikha (2022) conducted a study entitled "Measuring and validating the model of good governance with a sustainable development approach (a study in Sistan and Baluchistan)." The results revealed that in the proposed model, the index of comment and final responsibility, quality of laws, corruption control, the rule of law, and transparency are ranked first to fifth, respectively (Peyghan, Yaghobi & Keikha, 2020). Rezaei Lori, Selajeghe, and Maddahiyan (2022) conducted research entitled "Designing a good governance model for the systematic exploitation of Mines with a sustainable development approach (The case study of Golgohar Sirjan Industrial and Mineral Complex). The results revealed that comprehensive responsibility, a causal condition that includes intergenerational, environmental, and social obligations, causes the formation of good governance with future-oriented, health-oriented, and people-oriented characteristics. Along with the developmental space, creating opportunity and development-oriented strategies leads to sustainable social, economic, and environmental development (Rezaei Lori, Salajeghe & Maddahiyan, 2022). Xu and Zhu (2022) investigated the effects of green governance and green financial policies on sustainable development in various regions of China from 2008 to 2018. The results revealed that China's green governance index and green financial policies significantly reduced environmental pollution during the study period (Xu & Zhu, 2022). Shah, Lai, et al. (2021) conducted a study entitled "Development of a green governance framework to improve the performance of an oil and gas company." The results revealed that the proposed green governance framework reduced social costs and environmental risks and effectively improved the performance of the oil and gas industry (Shah, Lai, et al., 2021).   Methods This study is an applied type and analytical in terms of aim, qualitative in terms of process, and grounded theory in data collection and analysis method. A purposeful sampling method was used. Its data were collected using semi-structured interviews. The researcher achieved theoretical saturation after interviewing 12 experts. Also, data analysis and extraction of categories, related concepts, and semantic codes to answer the research questions in this study were done by MAXQDA software. Results This section answers the questions of providing a green governance model with a sustainable development approach in the health system (case study: Kerman University of Medical Sciences). The questions of this study were as follows: What are the causal conditions of providing a green governance model with a sustainable development approach in the health system? What are the contextual conditions for providing a green governance model with a sustainable development approach in the health system? What are the intervening conditions for providing a green governance model with a sustainable development approach in the health system? What are the strategies for presenting the model of green governance with a sustainable development approach in the health system? What is the outcome or implication of providing a green governance model with a sustainable development approach in the health system? The results revealed that the three components of "balanced and integrated management," "service provision," and "financial resources" were identified as causal factors. "Legal environment," "political environment," "cultural and social environment," and "technology" were identified as contextual factors. "Government policies" and "Transformation and change management" were identified as intervening factors. "Green governance affairs," "contractual affairs," and "participatory affairs" were identified as strategies. "Creating alignment between goals, policies, and structure and culture in the health sector," "improving administrative and environmental health," and "dynamism and adapting to changes and developments in the health system" were identified as outcomes. Discussion and Conclusion The present study provided a green governance model with a sustainable development approach in the health system. The results revealed that the causal factors are balanced and integrated management, providing services, and financial resources. The legal environment, political environment, cultural and social environment, and technology were found as the contextual factors. Intervening factors also included government policies and change management.